2014
DOI: 10.4236/mrc.2014.33013
|View full text |Cite
|
Sign up to set email alerts
|

Fischer-Tropsch Synthesis of the Promoted Co/ZSM-5 Hybrid Catalysts for the Production of Gasoline Range Hydrocarbons

Abstract: Fischer-Tropsch synthesis (FTS) reaction for the direct production of gasoline range hydrocarbons (C5-C9) from syngas was investigated on Ru, Pt, and La promoted Co/ZSM-5 (Si/Al = 25) catalysts. The hybrid catalysts were characterized by BET surface area, XRD, H2-TPR, NH3-TPD and XPS analyses. These physico-chemical properties were correlated with activity and selectivity of the catalysts. The promoted Co/ZSM-5 hybrid catalysts were found to be superior to the unpromoted Co/ZSM-5 catalyst in terms of better C5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…13 As reported in the literature, the use of alumina and silica supports may lead to formation of inactive iron species that then suppress the reducibility of iron oxide as a result of alumina and/or silica iron interaction. 43,48 The NH 3 -TPD profiles and related acid concentrations of catalysts are given in Figure 3a−c and Table 3, respectively. NH 3 -TPD profiles of USY and MOR supports are given in Figure S4a.…”
Section: Resultsmentioning
confidence: 99%
“…13 As reported in the literature, the use of alumina and silica supports may lead to formation of inactive iron species that then suppress the reducibility of iron oxide as a result of alumina and/or silica iron interaction. 43,48 The NH 3 -TPD profiles and related acid concentrations of catalysts are given in Figure 3a−c and Table 3, respectively. NH 3 -TPD profiles of USY and MOR supports are given in Figure S4a.…”
Section: Resultsmentioning
confidence: 99%
“…ZSM-5 particles with cobalt oxides can also enhance the extent of olefin cracking reaction of FTS products, and it increases the C 5 -C 22 hydrocarbon selectivity, as shown in Figure 27. Kang et al [118] also reported on the effect of a novel metal additive (Ru-nitrate, Pt-nitrate/chloride, and La-nitrate), as shown in Figure 28. Ryu et al later investigated the FTS reaction performance using Co-based catalysts supported on ZSM-5 with Ru, Pt, and La as co-catalysts [119].…”
Section: Zsm Supported Co-based Catalystmentioning
confidence: 98%
“…Effect of Promoter on the correlation between the surface activity and the selectivity of hydrocarbons. Reprinted with permission from[118].…”
mentioning
confidence: 99%
“…It was observed that almost all of the surface acidity of prepared catalysts are expected to have a beneficial effects on activity since there are an increase in the peak area and also shifts in both desorption peak to the lower temperature. According to [13] the weak acidic sites are responsible for FTS reaction and product distribution while the strong acidic sites, even are still on debate, is mainly contributed to dehydration of hydroxyl groups on surfaces. From Fig.…”
Section: Surface Acidity Of Modified Catalystmentioning
confidence: 99%